Mechanical Behaviors of Rice Husk and Boiled Egg Shell Particles Impregnated Coir‐Polyester Composites. Issue 1 (March 2016) - Bharathiraja, G.; Jayabal, S.; Kalyana Sundaram, S.; Rajamuneeswaran, S.; Manjunath, B. H.
Summary: This paper aims at improving the mechanical properties of coir fiber reinforced polyester composites through impregnation of rice husk and boiled egg shell in polyester matrix. The composites sheets were manufactured by varying the fabrication parameters such as fiber length, particulate content and fiber content. The mechanical properties of the fabricated composites were determined as per ASTM standards and the effects of fiber length, particulate content and fiber content on mechanical properties of rice husk and boiled egg shells impregnated coir ‐ polyester composites were studied. Scanning electron microscope analysis was used to characterize the fracture behavior of the composites. The investigation witnessed the improvement in mechanical properties on addition of rice husk particulate in coir fiber reinforced polyester composites. Similarly the addition of boiled egg shell in to the composites has enhanced mouldability of the composites. The SEM investigation evidenced the arrest of crack propagation and voids formation on addition of rice husk and egg shell particulates in polyester matrix. This study confirmed the possibility of using rice husk and boiled egg shell impregnated coir fiber reinforced polyester composites in low load bearing applications.